“Canva” Sebagai Media Pembelajaran Terkini Pengganti Power Point - Rizqi Abdillah (La-Tahzan: Jurnal Pendidikan Islam, 2022)
The rapid development of technology and information presents many alternative forms of learning media used. One of the learning media that has been too long or often used in learning is Power Point. But over time, the rapid development of technology and information can shift the existence of Power Point-based learning media. Where the media is too monotonous and less efficient in its use. One of the media that is present today, where its existence provides various ease of access and efficiency in its use, namely Canva media. This research uses the library research method by collecting data available in various existing sources. This research is expected to open insights, especially teachers in using learning media that is not monotonous and more up-to-date.